Influence of perceived customer satisfaction on on- line shopping experience during the COVID-19 pandemic - Malhan, Dr. Divya; Dr. Preeti ,; Mohan ,; Nisha, (The journal of contemporary issues in business and government, 2021)
Purpose:Customer satisfaction is always a great matter of concern for all the sellers and academicians that how the perceived satisfaction level of customers can be judged in case of online shopping. Present study is conducted in order to measure the level and to identify the most important factors which are contributing in measurement of theperceived customer satisfaction level towards online shopping experience during the COVID-19 pandemic. Research Methodology:Both primary and secondary data are included in the study. Statistical tool (SPSS-21) is used to run a statistical technique factor-analysis to identify most important factors while one way ANOVA is used to find out the significant difference between means of these factors and independence t-test is used to find out the significant difference between the two factors. Findings:This result showed that convenient and trust of online shopping, online shopping features and benefits, fair functioning, secure payment options, product information, positive online shopping experience and reliability of shopping were most important factors which significantly affect the perceived customers’ satisfaction toward online shopping during COVID- 19 pandemic andit also reveals that the demographic factors taken in the study do not show much of significant difference on satisfaction level of customers.